An improved biometric–based remote user authentication scheme for connected healthcare. (6th March 2015) - Mishra, Dheerendra; Chaturvedi, Ankita; Mukhopadhyay, Sourav
The advancements in technology have made the internet an efficient and scalable tool to utilise for various online services; one of them is connected healthcare. The connected healthcare system presents the platform to deliver clinical service door to door. In these online services, it is required to ensure the authenticity of patients to protect medical resources/services. In 2013, Chang et al. presented biometric–based remote user authentication scheme with user anonymity for connected healthcare. They claimed that their biometrics based scheme is secure and efficient to validate the legality of the patient. Recently, Das and Goswami demonstrated that Chang et al.'s scheme is vulnerable to insider attack and man–in–the middle attack. They also showed some flaws in login and password change phases of Chang et al.'s scheme. Furthermore, they presented an improved scheme. However, we observe that Das and Goswami's scheme does not provide three factor authentication and is vulnerable to offline identity guessing attack. Further, we propose an improved biometric–based remote user authentication scheme for connected healthcare, which provides efficient login and password change phases where smart card quickly identifies the incorrect input. Moreover, the proposed scheme satisfies all desirable security attributes and achieves three factor authentication.